Pengaruh Media Sosial Terhadap Keberadaan Insecure: Sebuah Analisis - Syauqii, Fachri (Communication & Social Media, 2022)
This research aims to analyze the influence of social media usage on the presence of insecurity among its users. In this digital era, social media has become a part of daily life, providing a platform for communication, information sharing, and social connections. However, excessive usage can have negative impacts on individuals' mental well-being, one of which is the presence of insecurity. This study utilizes an analytical approach to identify factors contributing to the existence of insecurity among social media users. The research methods employed include literature review and qualitative data analysis. The analysis results indicate that intensive social media usage and excessive focus on social comparisons can increase individuals' tendency to feel insecure. Continuous exposure to idealized portrayals of others' lives on social media can also lead to dissatisfaction with oneself and reinforce feelings of insecurity. Furthermore, the perception of social validation obtained from online interactions can create pressure and increase the need for validation from others, consequently amplifying the presence of insecurity.